Графічні засоби передачі невербальної інформації - Бабченко, Надія Володимирівна; Babchenko, N. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зроблено спробу описати причинно-наслідковий зв’язок між удосконаленням засобів зв’язку й пов’язаними з ним світоглядними змінами сучасної людини, з одного боку, та змінами у виборі графічних засобів, що використовуються для передачі невербальної інформації в інтернет-cпілкуванні. Актуальність теми зумовлена стабільним інтересом дослідників до орфографії й орфографіки, а також браком досліджень із цієї тематики. The article is an attempt to describe the cause-and-effect relationship between the changes in worldview of modern man and the changes in the choice of graphical means used in the online conversation. Relevance of the topic is due to stable interest of researchers to orthography and orthographics and the lack of research on the subject. The author concludes that the pecularities of use and interpretation of paragraphemic means used to transfer nonverbal graphical information may vary depending on the cultural identity of the recipient and the addressee and their familiarity with each other’s culture, and the culture in which this graphic sign was created. Understanding of paragraphemic signs requires analysis of the text content in conjunction with paragraphemics, a specific meaning of which is derived from the context and perception of the general idea of considering the possible implications and associations.
Graphical Means of Transmission of Nonverbal Information
Keywords: графіка; graphics; орфографія; orthography; орфографіка; orthographics